Relative age effects among student-athletes in a university high-performance programme: prevalence, annual variation and between-group comparisons - Dube, Sindiso Rangarirai (Stellenbosch : Stellenbosch University, 2022)
Thesis (M Sport Sc)--Stellenbosch University, 2022.